2022
DOI: 10.3390/su14116920
|View full text |Cite
|
Sign up to set email alerts
|

Social Cost-Benefit Analysis of Bottom-Up Spatial Planning in Shrinking Cities: A Case Study in The Netherlands

Abstract: In current research, the social return to citizens initiatives is important but often under-evaluated. Within this work, we collected the information that has emerged from measuring the social value of regenerative projects in shrinking cities. We used a case study of the regenerative project Gebrookerbos, a socio-spatial regeneration project in the shrinking city of Heerlen, the Netherlands. To assess the project’s monetary and immaterial aspects, a social cost–benefit analysis (SCBA) was used to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Due to a lack of public funds and interest from market parties, the municipality decided to follow a very different approach at the micro-level of the individual vacant sites in the district. Contrary to the usual approach to area (re)development with masterplans including well-defined goals and time horizons of 20-30 years, an open-ended bottom-up process was started as part of the Gebrookerbos project (see also Louali et al, 2022;Matoga, 2022). In this project, an independent intermediary or "broker" was appointed to coach residents of Heerlen-Noord who had ideas about new purposes for vacant sites in their neighborhood.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a lack of public funds and interest from market parties, the municipality decided to follow a very different approach at the micro-level of the individual vacant sites in the district. Contrary to the usual approach to area (re)development with masterplans including well-defined goals and time horizons of 20-30 years, an open-ended bottom-up process was started as part of the Gebrookerbos project (see also Louali et al, 2022;Matoga, 2022). In this project, an independent intermediary or "broker" was appointed to coach residents of Heerlen-Noord who had ideas about new purposes for vacant sites in their neighborhood.…”
Section: Contextmentioning
confidence: 99%
“…The large majority of the ideas that are realized aim at the development of social and/or ecological values. An overall societal cost-benefit analysis of the Gebrookerbos initiatives conducted by Louali et al (2022), showed that for the municipality the financial balance in terms of expenses (mainly time invested by municipal and project employees) and cost savings (mainly tasks conducted by citizen-volunteers) was negative. The Schurenbergerpark is no exception in this respect.…”
Section: Economic Outcomesmentioning
confidence: 99%
“…There is some recent work on the Cost Benefit Analysis of Public Services in urban areas. How they evolve in shrinking cities (Louali et al, 2022); in sprawling cities (Lityński, 2022), and in the design and management of smart cities (Egin & Treleaven, 2019;Turečková & Nevina, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, citizen participation is seen as a crucial and undisputable factor for legitimizing regeneration projects and ensuring their successful implementation. Likewise, it is widely accepted that the regeneration of shrinking cities calls for new governance agreements between (local) governments and societal partners [11][12][13][14]. Involving residents in transformation of an area is not only seen as desirable but is also legislated by the Dutch government [15]: citizen participation is required if a regeneration project is to be initiated and conducted.…”
Section: Introductionmentioning
confidence: 99%